ABUNDANCE AND OCCURRENCE OF PHOSPHATE SOLUBILIZING BACTERIA AND PHOSPHATASE IN SEDIMENT OF HOOGHLY ESTUARY, NORTH EAST COAST OF BAY OF BENGAL, INDIA - T. K. De; T. K. Sarkar; M. De; T. K. Maity; A. Mukherjee; S. Das (JOURNAL OF COASTAL DEVELOPMENT, 2011)
The abundance and occurrence of a special group of bacteria, capable of solubilizing or mobilizing insoluble phosphates were studied in estuarine environment, especially in sediments. The possible role of various factors of the sediments in maintaining the phosphate availability in the overlying water was described. The phosphatase activity was recorded in all samples irrespective of salinity variations. Total number of bacteria showed higher value in lower salinity. The total phosphate content in soil showed positive correlation with the phosphatase activity ( r = 0.890; P-Value = 0.000; n-=15). Clayey sediment contents more phosphate solubilizing bacteria and phosphatase than sandy sediment in a tropical estuarine region of River Hooghly.